Upaya Meningkatkan Permainan Lempar Lembing Kids Athletic Menggunkan Alat Modifikasi Plastic Polivinil Clorida (PVC) - Wildan Nasrullah; Dicky Reva Apriana Sanga (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study was prompted by the low levels of interest, motivation and learning outcomes among pupils in javelin throwing (kids’ athletics) in Year 5 at SD Negeri 3 Cisantana. The aim of this study was to improve learning outcomes in javelin throwing through the application of a game-based approach using modified equipment made from polyvinyl chloride (PVC). The research method used was Classroom Action Research (CAR), conducted in two cycles, each comprising the planning, implementation, observation, and reflection stages. The research subjects consisted of 15 Year 5 pupils. Data collection techniques included tests, observation, and documentation, whilst data analysis was conducted using quantitative descriptive methods. The research results showed an improvement in student learning outcomes, as indicated by the percentage of learning achievement in Cycle I of 26.67% with an average score of 67.19, which then increased in Cycle II to 80.00% with an average score of 79.73. Based on this improvement in achievement rates and average scores, it can be concluded that the application of a game-based approach using modified PVC equipment is effective in improving students’ javelin-throwing performance, accompanied by increased interest and engagement during the learning process